Implementation Science: Increasing the Public Health Impact of Audiology Research. - Studts, Christina R. (American Journal of Audiology)
Purpose: Implementation science aims to facilitate the use of evidence-based programs, practices, and policies in routine care settings. In audiology, as in other health disciplines, there is a persistent research-to-practice gap. Improving the adoption, reach, implementation, and sustainment of effective interventions in audiology would increase their public health impact, ensuring that all individuals needing hearing health care services could benefit from innovations and evidence-based best practices. This tutorial provides an introductory overview of implementation science relevant to the field of audiology, including Internet-based practices and interventions. Method: Major concepts and themes of implementation science are presented, including implementation outcomes, implementation science frameworks, implementation strategies, current topics in implementation science, and study design considerations. Recent publications in audiology are highlighted to illustrate implementation science concepts and themes. The relevance of each topic to the use of evidence-based programs, practices, and policies in audiology is highlighted with reference to recent research in the field. Conclusions: Challenges in the widespread delivery of evidence-based audiological practices and interventions limit their public health impact. The application of implementation science principles and methods in audiology research, as demonstrated in other areas of health research, can increase our focus on ensuring that effective practices are widely available, accessible, equitable, and sustainable to improve the lives of those who need them.